Optimization of the arrangement of ring-spice-rod fixators on the experimental data base during the treatment of tibia nonunion - Maxim Baida; Anatoliy Rushay; Alexander Martinchuk; Olha Musiienko (Bogomolets National Medical University, 2022)
the problem of tibial bone non-unions after fractures is an actual and not finally solved problem. The use of ring spoke-rod devices is the leading method of treatment. Improvement of this technology is a generally accepted direction to improve the results of treatment. The aim of the work was to improve the results of the treatment of non-unions of the lower leg bones based on the improvement of the fixation technology of ring retainers. In order to fulfill the task of the research, the problematic issues of fixation of non-unions of lower leg bones after fractures with spoke-rod ring devices were studied; the formulated concept of solving the existing shortcomings of the method in the experiment; clinical applications and analysis of the obtained results. The influence of the spatial fixation of the rod in the ring fixator of the spoke-rod type was determined experimentally. The subject of the study was a Sawbones® synthetic bone with a fracture model, which was fixed with a ring fixator of the spoke-rod type by 2 models. In our "apparatus-bone" fixation experiment, all the main parameters of both models (number of rings, spokes, angles of intersection of spokes and fracture planes) were similar. The difference between the two models was only in the presence or absence of a stiffener for fixing the rod. 60 victims met the criteria for inclusion in the study. 31 patients were operated on with the use of ring devices with increased rigidity of rod fixation according to the proposed method; they formed the main group. 29 patients - the comparison group, the treatment was carried out according to the generally accepted method using fixation of the rod without a rib of "stiffness". Clinical evaluation of the results was carried out using the anatomic-functional scale of the Modified Functional Evaluation System by Karlstrom-Olerud. The obtained experimental data indicated an improvement in the stiffness parameters of the spoke-rod system when using rod fixation with a stiffening rib. The greatest effect was obtained during the bending test - the indicator increased from 0.91 to 1.19 H/mm (by 23.53%). The results of clinical effectiveness obtained by us (good and excellent 77.8%; unsatisfactory in 2.8%) can be compared with the data of most researchers. Anatomic-functional results in the main group with a high probability (95%) exceeded the results in the comparison group. Experimental data were confirmed by clinical results. The anatomic-functional results in the main group according to the values of the estimated anatomic-functional scale of the Modified Functional Evaluation System by Karlstrom-Olerud with a high probability (>95%) exceeded the results in the comparison group. Bearing in mind the severity of the lesion, we consider the obtained clinical results to be encouraging. Application of the proposed improvements and further investigation of their effectiveness should be recommended.